Nocturnal and morning asthma. Relationship to plasma corticosteroids and response to cortisol infusion. - C A Soutar; J Costello; O. Ijaduola; M Turner‐Warwick (1975)
Nocturnal and early morning breathlessness is a common and important symptom in asthmatic patients. Six patients in whom these symptoms were a major clinical problem have been studied by serial measurements of peak expiratory flow rate (PEFR) and plasma corticosteroids over two 24-hour periods. Although PEFR and plasma corticosteroids are lowest during the night or early morning, preventing the nocturnal fall in plasma corticosteroids by cortisol infusion did not prevent the fall in PEFR in five out of the six patients. The circadian rhythm of corticosteroid secretion does not appear to be the main cause of nocturnal and early morning asthma.